2016
DOI: 10.1080/02626667.2015.1051485
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China

Abstract: A new physics-based rainfall-runoff method of SWAT was developed, which integrates a water balance model (WB proposed by White et al. (2011)) with the variable source area (WB-VSA). This approach was further compared with four methods -soil-water-dependent curve number (CN-Soil), evaporation-dependent curve number (CN-ET), Green and Ampt equation (G&A) and WB -in a monsoonal watershed, Eastern China. The regional sensitivity analysis shows that volumetric efficiency coefficient (VE) with river discharges is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…African catchments mainly prompted this study, it has also been noted that other modellers have recently addressed similar issues with other models (Boll, Brooks, Crabtree, Dun, & Steenhuis, 2015;Cheng et al, 2016;Woodbury, Shoemaker, Easton, & Cowan, 2014).…”
Section: Although Some Recent Experiences Of Applying the Model In Somentioning
confidence: 83%
See 1 more Smart Citation
“…African catchments mainly prompted this study, it has also been noted that other modellers have recently addressed similar issues with other models (Boll, Brooks, Crabtree, Dun, & Steenhuis, 2015;Cheng et al, 2016;Woodbury, Shoemaker, Easton, & Cowan, 2014).…”
Section: Although Some Recent Experiences Of Applying the Model In Somentioning
confidence: 83%
“…The new process referred to is the generation of surface run‐off due to saturation excess. Although some recent experiences of applying the model in southern African catchments mainly prompted this study, it has also been noted that other modellers have recently addressed similar issues with other models (Boll, Brooks, Crabtree, Dun, & Steenhuis, ; Cheng et al, ; Woodbury, Shoemaker, Easton, & Cowan, ).…”
Section: Introductionmentioning
confidence: 92%
“…However, there are some controversies with this method: it is not physically based, it lacks complete historical documentation, and it inadequately represents variable source areas (VSA). It also provides inadequate consideration of the rainfall intensity and duration on runoff generation [2,[11][12][13]. Many researchers have proposed adjustments to the CN model to better capture runoff dynamics [8,12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It also provides inadequate consideration of the rainfall intensity and duration on runoff generation [2,[11][12][13]. Many researchers have proposed adjustments to the CN model to better capture runoff dynamics [8,12,[14][15][16][17]. For example, White et al [15] found that temporal CN adjustments resulted in more accurate simulations, when the CN in the Soil and Water Assessment Tool (SWAT) was changed seasonally to account for variation of watershed storage due to changes in plant growth and dormancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation